(untitled) (Vietnam Journal of Community Medicine, 2023)
Background: Type 2 diabetes mellitus (T2DM) is a popular condition and cardiovascular risk factor in Vietnam. Thanks to advanced diagnostic and treatment methods, individuals with T2DM have an extended life expectancy. However, this comes with increased diabetes-related complications, including cardiovascular diseases. Understanding cardiovascular risk and cardiovascular disease characteristics is essential in effectively caring for individuals with T2DM. Aims: The study was conducted to estimate the global cardiovascular risk and cardiovascular disease in T2DM patients at outpatient clinics. Method: A descriptive cross-sectional study was conducted at the endocrinology clinic and cardiology clinic of Nhan Dan Gia Dinh Hospital from March 2021 to March 2022. The hospital’s Ethics Committee approved the study with protocol number 37/NDGĐ-HĐĐĐ dated 30/3/2022 Results: A total of 515 patients participated in the study, with an average age of 66, higher in the cardiology clinic than the endocrinology clinic. Female gender dominance was observed in both clinics. Cardiovascular risk ranged from high to very high and differed between the two clinics, with high risk being predominant in the endocrinology clinic and very high risk being predominant in the cardiology clinic. Cardiovascular diseases included Coronary artery disease at 47.8%, stroke at 2.5%, heart failure at 4.9%, and peripheral artery disease at 0.6%. Conclusion: T2DM patients receiving outpatient treatment at Nhan Dan Gia Dinh Hospital have a cardiovascular risk ranging from high to very high, with a notable prevalence of cardiovascular disease, even in the endocrinology clinic. Therefore, comprehensive control of cardiovascular risk factors and appropriate selection of blood glucose-lowering treatments for this high-risk group are crucial.